FAKTOR-FAKTOR YANG MEMPENGARUHI PERSEPSI WAJIB PAJAK MENGENAI PENGGELAPAN PAJAK (TAX EVASION) - Beny Prastomo, 11.05.52.0035; Wahyudi, Djoko (Students' Journal of Accounting and Banking, 2017)
Government will continue to improve domestic revenue sources in order to development of the country. From this sector, the Government continues to improve the acceptance of the State in which that is the mainstay of revenues from taxes. The purpose of this study was to analyze the factors influencing perceptions regarding taxpayers of tax fraud (tax evasion) ". As for the population in this study population in this study is an individual taxpayer in the Tax Office Primary Semarang Candisari many as 71,900. The sample in this study were selected using purposive sampling method, which means the withdrawal or the selection of random samples that have specific goals or targets. The analysis tool used is multiple linear regression. The results showed that the Justice and discrimination have a positive influence on the perception of taxpayers regarding tax evasion. While perpajaka system and quality of service negatively affect the perception of taxpayers regarding tax evasion.Keywords: Justice, Taxation System, Discrimination, Quality Of Service has an influence on the perception of Taxpayers regarding Tax Evasion